Restrukturisasi Subsidi Jaminan Kesehatan dan Dampaknya Terhadap Stabilitas Sosial - Supendi Samian; Bagus Margono (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The decile-based restructuring of the National Health Insurance (JKN) subsidy is a government policy aimed at improving fiscal efficiency and targeting of premium assistance recipients (PBI). This policy uses the welfare decile classification from the Integrated Social Welfare Data (DTKS) as the basis for determining subsidy participation. This study aims to analyze the design of the subsidy restructuring policy, its impact on social stability, and its implications within the framework of the welfare state. The study employed a qualitative approach with a policy analysis design through literature review and analysis of official documents. Data were analyzed using an interactive model that encompasses data reduction, data presentation, and conclusion drawing. The results indicate that decile-based subsidy restructuring has the potential to improve budget efficiency and support the fiscal sustainability of the JKN program. However, the reliance on data validity and the risk of exclusion errors can have social impacts such as uncertainty about access to health services, decreased perceptions of distributive justice, and weakened public trust. From a welfare state perspective, this policy demonstrates a shift from a universal approach to a residual approach, potentially impacting social cohesion. This study concludes that the success of subsidy restructuring is determined not only by fiscal rationality, but also by the quality of governance, data transparency, and participatory mechanisms capable of maintaining social stability.